Geosites and geotouristic attractions proposed for the Project Geopark Colca and Volcanoes of Andagua, Peru - Galas, Andrzej (2018)
The Colca Canyon (Central Andes, Southern Peru), about 100 km long and 1–3 km deep, forms a magnificent cross section of the Earth’s crust giving insight into mutual relations between lithostratigraphical units, and allowing relatively easy interpretation of the fascinating geological history written in the rocky beds and relief. Current activity of tectonic processes related to the subduction of the Nazca plate beneath the South American Plate exposed the geological heritage within study area. Welldeveloped tectonic structures present high scientific values. The volcanic landforms in the Valley of the Volcanoes and around the Colca Canyon include lava flows, scoria cones and small lava domes. They represent natural phenomena which gained recognition among tourists, scientists and local people. Studies performed by the Polish Scientific Expedition to Peru since 2003 recognized in area of Colca Canyon and Valley of the Volcanoes high geodiversity, potential for geoturism but also requirements for protectection. The idea of creating geopark gained recently the approval of regional and local authorities with support from the local National Geological Survey (INGEMMET). The Geopark Colca and Volcanoes of Andagua would strengthen the relatively poor system of the protected areas in the Arequipa department, increasing the touristic attractiveness and determine constraints for sustained regional development.